Analysis of IEEE 802.15.4 Beacon-Enabled MAC Protocol - Nga Dinh; Sangsoon Lim (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper aims to develop several mathematical models to study medium access control (MAC) protocol in the IEEE 802.15.4 beacon-enabled mode with star topology. In particular, the MAC protocol which employs a slotted carrier-sense multiple access with collision avoidance (CSMA/CA) algorithm used in the contention access period (CAP) of a superframe is modelled. The analysis studies the effectiveness of the CSMA/CA algorithm and provides explicit mathematical expressions for power consumption, access delay, and data frame drop probability. The proposed models precisely follow CSMA/CA algorithm in MAC protocol of beacon-enabled mode and differ from those previously published in the literature as 1) they are derived based on data frame generation rate of end devices, 2) they provide a completed expression for frame access delay, and 3) lowpower states of end devices are considered for power efficiency evaluations. The paper shows how power consumption of end devices is improved on the balance with data frame delay. The validity of the proposed models is confirmed and complemented by extensive simulations.